2021
DOI: 10.3390/vaccines9050416
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Intent and Willingness to Pay in Bangladesh: A Cross-Sectional Study

Abstract: This article reports the intent to receive a SARS-COV-2 vaccine, its predictors and willingness to pay in Bangladesh. We carried out an online cross-sectional survey of 697 adults from the general population of Bangladesh in January 2021. A structured questionnaire was used to assess vaccination intent. The questionnaire included sociodemographic variables and health belief model constructs which may predict vaccination intent. Among the participants, 26% demonstrated a definite intent, 43% probable intent, 24… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
6
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 42 publications
11
82
6
4
Order By: Relevance
“…Our findings provide another piece of evidence that shows the low intention to get vaccinated in Hong Kong when compared to other countries in the world. For instance, other research has shown high vaccination intention or acceptance in the U.S. (62–75%) [ 17 , 24 , 25 ], UK (64%) [ 26 ], Australia (86%) [ 27 ], France (77–78%) [ 28 , 29 ], Japan (62–66%) [ 30 , 31 ], Bangladesh (69%) [ 32 ], Israel (80%) [ 18 ], and India (89%) [ 33 ]. Even when we compared the rates within the Chinese population, intention to receive COVID-19 vaccines in Hong Kong is among the bottom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings provide another piece of evidence that shows the low intention to get vaccinated in Hong Kong when compared to other countries in the world. For instance, other research has shown high vaccination intention or acceptance in the U.S. (62–75%) [ 17 , 24 , 25 ], UK (64%) [ 26 ], Australia (86%) [ 27 ], France (77–78%) [ 28 , 29 ], Japan (62–66%) [ 30 , 31 ], Bangladesh (69%) [ 32 ], Israel (80%) [ 18 ], and India (89%) [ 33 ]. Even when we compared the rates within the Chinese population, intention to receive COVID-19 vaccines in Hong Kong is among the bottom.…”
Section: Discussionmentioning
confidence: 99%
“…As women, in general, tend to express greater worry and fear of the side effects of the vaccines [ 19 ], a greater vaccine hesitancy and refusal among them could be expected. Older age is another significant demographic factor that has been consistently demonstrated as a predictor to higher intention to receive COVID-19 vaccines [ 28 , 32 ]. Age may affect intention to vaccinate in several ways.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil temuan penelitian ini dengan demikian sesuai dengan teori analisis HBM yang mengungkapkan bahwa keparahan yang dirasakan terkait dengan minat untuk menerima vaksin. Sehingga individu yang menganggap covid-19 sangat serius lebih mungkin untuk divaksinasi (Kabir et al, 2021). Dengan demikian, Hasil ini mengindikasikan bahwa tinggi dan rendahnya minat untuk melakukan vaksinasi covid-19 berkaitan erat dengan tinggi dan rendahnya keparahan yang dirasakan oleh masyarakat Muslim di Yogyakarta.…”
Section: Pengaruh Keparahan Yang Dirasakan Terhadap Minat Vaksinasi Covid-19unclassified
“…This study was conducted in a very difficult global crisis, during the ongoing lengthy coronavirus disease 2019 (COVID-19) pandemic and partial lockdown situation, so collecting more detailed information about the specific issues highlighted in the study was not practically possible. We conducted studies on native Bangladeshi dentists’ knowledge on COVID-19 [ 39 ] and clinical practice during the pandemic, and on intentions to receive the COVID-19 vaccine of the general Bangladeshi population [ 40 ]. However, we could not collect these data for the non-native IUDSs due to time limitations and the closure of institutes due to lockdown.…”
Section: Strengths and Limitationsmentioning
confidence: 99%